FEATURES OF BUSINESS ORGANIZATION DEVELOPMENT MANAGEMENT IN MODERN UKRAINIAN CONDITIONS (Development Service Industry Management, 2023)
The article delves into a comprehensive exploration aimed at evaluating the efficacy of diverse tools and measures employed in the management of business organization development, particularly in the challenging context of military aggression. The research expands upon the conventional understanding of "development management" but also analyzes the intricate interplay between operational and strategic instruments.An examination of operational tools, such as inventory management, production planning, and financial oversight, reveals their crucial role in providing businesses with the agility needed to navigate the immediate challenges imposed by military conflicts. These tools contribute significantly to the short-term stability of business operations, offering adaptive solutions to address evolving circumstances promptly.Concurrently, the study delves into the strategic dimension of development management, emphasizing the paramount importance of long-term planning and adaptability. Strategic tools, including SWOT analysis, innovation analysis, change management strategies, and project management frameworks, are highlighted as integral components for sustaining and advancing business organizations during periods of military aggression.The article demonstrates that a synergistic approach, harmonizing both operational and strategic tools, is imperative for the successful management of business development in such tumultuous conditions. The ability to strike a delicate balance between short-term resilience and long-term adaptability emerges as a critical factor for organizational survival and growth in the face of adversarial circumstances.By providing insights into the intricacies of effective management strategies, the future research can contribute to the broader discourse on organizational resilience, offering practical implications for navigating complex environments.
Keywords: development; development management; sustainable development; business environment; adaptation; operational and strategic tools